2022
DOI: 10.3390/biomedicines10071696
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of the Epidemiological Features and Clinical Significance of Renal Hypouricemia

Abstract: A genetic defect in urate transporter 1 (URAT1) is the major cause of renal hypouricemia (RHUC). Although RHUC is detected using a serum uric acid (UA) concentration <2.0 mg/dL, the relationship between the genetic state of URAT1 and serum UA concentration is not clear. Homozygosity and compound heterozygosity with respect to mutant URAT1 alleles are associated with a serum UA concentration of <1.0 mg/dL and are present at a prevalence of ~0.1% in Japan. In heterozygous individuals, the prevalence of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Increased 8-OHdG levels were noted in cardiovascular diseases, kidney disease in individuals with type 1 diabetes, and colorectal or serous ovarian cancer [ 222 , 223 , 224 , 225 ]. Hypouricemia may be caused by decreased uric acid production, uric acid oxidation due to treatment with uricase, or decreased renal tubular reabsorption due to inherited or acquired disorders [ 226 , 227 ]. Serum lysine levels (besides other AA) seem to be stable during diet changes, for example, the oxidation of lysine is at similar levels in humans with protein restriction [ 228 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased 8-OHdG levels were noted in cardiovascular diseases, kidney disease in individuals with type 1 diabetes, and colorectal or serous ovarian cancer [ 222 , 223 , 224 , 225 ]. Hypouricemia may be caused by decreased uric acid production, uric acid oxidation due to treatment with uricase, or decreased renal tubular reabsorption due to inherited or acquired disorders [ 226 , 227 ]. Serum lysine levels (besides other AA) seem to be stable during diet changes, for example, the oxidation of lysine is at similar levels in humans with protein restriction [ 228 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enomoto and coworkers characterized 3 index cases: one with a nonsense mutation (W258X) and two with missense mutations (T217M and E298D) 35 . Since the original description by Enomoto et al, more than 30 mutations causing familial renal hypouricemia have been reported 42 . This condition occurs at higher frequencies in Japanese, Iraqi Jews, and Roma 43–45 .…”
Section: Individual Ua Transportersmentioning
confidence: 99%
“…This condition occurs at higher frequencies in Japanese, Iraqi Jews, and Roma 43–45 . The higher frequency among the Japanese and the Roma has been attributed to a founder effect in those populations 42 . Genome‐wide association studies (GWAS) have yielded URAT1 polymorphisms in other populations as well 46 .…”
Section: Individual Ua Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the cellular transport system of uric acid, it is known that in humans, almost all uric acid is filtered by the glomeruli and reabsorbed from the renal tubules through transporter subunits present on the surface of the glomerular lumen (URAT 1), before reaching the basolateral membrane where the URATv1 transporter is located, which plays an important role in uric acid absorption in endothelial cells [ 27 , 28 ]. Experimental studies have shown that uric acid transporters are also expressed in vascular endothelial cells, contributing to inflammation; oxidative stress; and, hence, endothelial dysfunction through a reduction in endothelial NO [ 29 , 30 ].…”
Section: Endothelial Dysfunction and Hyperuricemiamentioning
confidence: 99%